Thick as thieves - Brown, Sandra 1948- (New York Grand Central Publishing, 2020)
Twenty years ago four individuals pulled a heist and almost walked away with half a million dollars. By daybreak one was in the hospital; one was in jail; one was dead. And one got away with it. Arden Maxwell, a daughter of the man who disappeared, has never reconciled with her father's abandonment of her and her sister. Returning to her family home near Caddo Lake, she finally get answers to the many questions that torment her. Unfortunately two of her father's co-conspirators are watching her every move. Ledge Burnet is back in town to care for his ailing father - and to keep his eye on the county's corrupt district attorney, whom he suspects was the real murderer. Arden's presence ignites Ledge's determination to expose the D.A.'s treachery - and sparks a desire he wishes to deny. -- adapted from jacket
109397
Keywords: Fathers and daughters -- Fiction; Missing persons -- Fiction; Thieves -- Fiction; Murder -- Fiction; Man-woman relationships -- Fiction; Fiction / Thrillers / Suspense; Fiction / Romance / Suspense; Fiction / Crime; Romantic suspense fiction; Detective and mystery fiction; Fiction; Thrillers (Fiction); Suspense fiction; Mystery fiction